Hak Ijbâr Wali Nikah dalam Perspektif Hukum Perkawinan Indonesia dan Kesetaraan Gender - Muhammad Nabil (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2020)
Choosing a candidate in marriage is a very principle matter, whether the candidate is the choice of himself or someone else's choice (in this case the guardian / parent with the right of consent). Meanwhile, recently the discourse of gender justice has become a topic of discussion in the midst of society. With the gender discourse, the right to consent of wali is also a topic of debate. Therefore, to respond to this, this research raises at least two fundamental questions, namely whether the right to ijbar in Islamic jurisprudence is still relevant to current conditions and how the right of ijbâr according to marriage law (UUP and KHI). From the results of this study that in Islamic jurisprudence the right to ijbar is a form of protection for parents (guardians) to marry off their children as a form of responsibility. Meanwhile, differences of opinion from each Islamic jurisprudence group except Hanafiyah allow guardians to marry off their children as a responsibility with several terms and conditions. Meanwhile, Article 6 paragraph 1 states that marriage must be based on the agreement of the bride and groom. This is in line with KHI article 16 paragraphs 1 and 2 which explicitly states the necessity to obtain consent, whether oral, written or a statement indicating that his silence is his agreement. However, if the opposite is true, the marriage cannot be carried out. It can be said that the right of a wali nikah consent is not absolute because the guardian must have the consent of his child